Volume 5B: 42nd Mechanisms and Robotics Conference 2018
DOI: 10.1115/detc2018-86261
|View full text |Cite
|
Sign up to set email alerts
|

Energy Absorption of Origami Crash Box: Numerical Simulation and Theoretical Analysis

Abstract: Thin-walled tubes as energy absorption devices are widely in use for their low cost and high manufacturability. Employing origami technique on a tube enables induction of a predetermined failure mode so as to improve its energy absorption efficiency. Here we study the energy absorption of a hexagonal tubular device named the origami crash box numerically and theoretically. Numerical simulations of the quasi-static axial crushing show that the pattern triggers a diamond-shaped mode, leading to a substantial inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Many efforts have been thus taken to reduce the initial peak force while keeping or increasing the absorbed energy, ranging from introducing dents and grooves (Mamalis et al, 1986;Yang et al, 2017), corrugations (Singace and El-Sobky, 1997;Wu et al, 2016) into square and circular tubes. Lately, researchers have found that the introduction of origami patterns into thin-wall structures can trigger specific failure modes, which in turn change the structural responses and characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Many efforts have been thus taken to reduce the initial peak force while keeping or increasing the absorbed energy, ranging from introducing dents and grooves (Mamalis et al, 1986;Yang et al, 2017), corrugations (Singace and El-Sobky, 1997;Wu et al, 2016) into square and circular tubes. Lately, researchers have found that the introduction of origami patterns into thin-wall structures can trigger specific failure modes, which in turn change the structural responses and characteristics.…”
Section: Introductionmentioning
confidence: 99%